The Identification of Carotenoids and Testing of Carotenoid Antioxidants from Sand Lobster (Panulirus homarus) Egg Extract - James Ngginak; Jubhar C Mangibulude; Ferdy S Rondonuwu (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
Sand lobsters (Panulirus homarus) are organisms that play an important role in supporting a society’s economy. Lobsters have a business appeal due to their high demand, enjoyable taste, as well as significant nutritional content. It is interesting that sand lobster eggs have a yellow orange color as an indicator of the presence of carotenoid content. Related with advancements in research and the utilization of carotenoids, this research identifies carotenoids and tests carotenoid antioxidants from sand lobster (Panulirus homarus) egg extract. In identifying carotenoids in sand lobster egg extract, HPLC (high performance liquid chromatography) (shimadzu LC-10AD, Japan) is used. In testing carotenoid antioxidants from sand lobster eggs, a DPPH method is utilized. The identification results with HPLC reveal that the sample contains carotenoids. The kinds of carotenoids identified are dinoxanthin, diadinoxanthin, zeaxanthin, lutein, astaxanthin, and violaxanthin. Among the six kinds of carotenoids identified, lutein is the type of carotenoid that has the highest concentration. These carotenoid compounds are detected in wavelengths of 400-500 nm. The test results of antioxidant power reveal that to hamper free radicals (IC50), a sample concentration of 6675.25 µg.ml-1 is needed. The ability to hinder free radicals from a sample extract is mostly conducted by lutein, zeaxanthin, and astaxantin. If seen from the analytical results, it can be surmised that sand lobster eggs contain carotenoids that can be used as a carotenoid source for humans.   Keywords : Sand Lobster, HPLC, Carotenoids, DPPH, Antioxidant